Chemical synthesis of perfectly isotactic and high melting bacterial poly(3-hydroxybutyrate) from bio-sourced racemic cyclic diolide - Xiaoyan Tang; Eugene Y.-X. Chen (Nature Communications, 2018)
Bacterial poly(3-hydroxybutyrate) possesses physical and mechanical properties suitable for substituting high-performance petroleum plastics but current production is costly and slow. Here the authors produce poly(3-hydroxybutyrate) with similar properties via ring-opening polymerization of bio-derived racemic cyclic diolide.